Balancing mining and the environment : South Africa’s legal framework concerning pollution caused by mining, with examples from the West Rand and Emalahleni. - Knutton, Keeley Marie (Stellenbosch : Stellenbosch University, 2023)
Thesis (LLM)--Stellenbosch University, 2023.